Differences in clinico-pathological characteristics and outcomes between proteinase 3-ANCA positivity and myeloperoxidase-ANCA positivity in lupus nephritis. (August 2019) - Li, C; Wang, J -J; Zhou, M -L; Liang, D -D; Yang, J; Zhu, H -X; Hu, W -X; Zhang, H -T
Background: Owing to the low prevalence of anti-neutrophil cytoplasmic antibodies (ANCA) in lupus nephritis (LN), there is no study about the differences between proteinase 3 (PR3)-ANCA positivity and myeloperoxidase (MPO)-ANCA positivity in LN until now. Methods: Here we perform a retrospective study to determine whether there are differences in clinic-pathological characteristics and renal outcomes between PR3-ANCA-positive LN patients and MPO-ANCA-positive LN patients. Results: A total of 26 (27.4%) PR3-ANCA-positive LN patients and 69 (72.6%) MPO-ANCA-positive LN patients ( p < 0.001) were eligible for this study. Compared with PR3-ANCA-positive LN patients, MPO-ANCA-positive LN patients had significantly higher levels of serum creatinine (109.6 µmol/l vs. 74.3 µmol/l, p = 0.02), lower titers of antinuclear antibodies (ANA) (128 vs. 256, p = 0.01), and higher serum concentrations of C3 and C4 (0.54 g/l vs. 0.36 g/l, p = 0.002; 0.12 g/l vs. 0.06 g/l, p < 0.001; respectively). Furthermore, the MPO-ANCA-positive group had higher scores for chronicity index ( p = 0.007), including interstitial fibrosis ( p = 0.001) and tubular atrophy ( p = 0.03) on biopsy specimens. The renal survival rates for MPO-ANCA-positive LN patients were 94.1% at 1 year, 83.2% at 5 years and 79.6% at 10 years; these values were worse when compared with those of the PR3-ANCA-positive group, which were 100%, 100% and 100%, respectively. Conclusion: MPO-ANCA-positive LN patients had more severely impaired baseline renal function and less active lupus serology. More severely chronic pathological changes, including interstitial fibrosis and tubular atrophy on renal specimens, occurred in MPO-ANCA-positive LN patients. We found that MPO-ANCA-positive LN patients had worse renal outcomes.